UV irradiation-induced production of monoglycosylated biglycan through downregulation of xylosyltransferase 1 in cultured human dermal fibroblasts. Issue 1 (July 2015) - Jin, Cheng Long; Oh, Jang-Hee; Han, Mira; Shin, Min Kyeong; Yao, Cheng; Park, Chi-Hyun; Jin, Zhe Hu; Chung, Jin Ho
Highlights UV increases monoglycosylated biglycan production in cultured fibroblasts. UV decreases XYLT1 mRNA expression much more than XYLT2. Only XYLT1 donwregulation induces monoglycosylated biglycan production. XYTL2 seems to react with only serine 42 but not with serine 47 on the biglycan core protein.